PRINCIPLES PROVIDING THE EFFICIENCY OF TECHNOLOGIES FOR USING ADAPTIVE MOTOR RECREATION AND ADAPTIVE SPORT - Evseev S.P. ,; Shelekhov A.A. ,; Evseeva O.E. ,; Aksenov A.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the general principles that ensure the effectiveness of technologies for the use of adaptive motor recreation and adaptive sports. Methods and structure of the study. To achieve this goal, an analysis of modern scientific publications, legal documents, dissertations devoted to the problem of implementing classes in adaptive motor recreation and adaptive sports was carried out. The search depth was 10 years. Results and conclusions. In the process of working on the definition of such a fundamental category for adaptive physical culture, the principle, the authors adopted an approach according to which this concept is interpreted as the main, guiding position that determines the content and implementation of practical activities. As a result of the analysis and systematization of scientific and practical knowledge in the field of adaptive physical culture, a team of authors identified six general principles, the observance of which should ensure the effectiveness of technologies for the use of adaptive motor recreation and adaptive sports.